2015
DOI: 10.1378/chest.14-1530
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following Therapeutic Bronchoscopy for Malignant Central Airway Obstruction

Abstract: and Michael Simoff , MD , FCCP ; on behalf of the AQuIRE Bronchoscopy Registry BACKGROUND: Th ere are signifi cant variations in how therapeutic bronchoscopy for malignant airway obstruction is performed. Relatively few studies have compared how these approaches aff ect the incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 36 publications
7
112
4
3
Order By: Relevance
“…While there were no fatal procedural complications in this study, the overall rate of fatal procedural complications reported in AQuIRE was 0.5% 27. The overall risk-benefit ratio of therapeutic bronchoscopy is very favourable if we use 0.5% as our estimate of fatal procedural complications and consider ∆utility-long-term as roughly a 5.8% improvement over baseline.…”
Section: Discussionmentioning
confidence: 65%
“…While there were no fatal procedural complications in this study, the overall rate of fatal procedural complications reported in AQuIRE was 0.5% 27. The overall risk-benefit ratio of therapeutic bronchoscopy is very favourable if we use 0.5% as our estimate of fatal procedural complications and consider ∆utility-long-term as roughly a 5.8% improvement over baseline.…”
Section: Discussionmentioning
confidence: 65%
“…They also found that the complication rate was higher in those with ASA >3, re-do bronchoscopy, receiving procedure under emergent or urgent situation. Thirty-day mortality was associated with poor performance status and ASA >3 (60). However, the patients with higher baseline Borg score had the greater improvement in dyspnea and quality of life.…”
Section: Developing Stentsmentioning
confidence: 94%
“…Interventional bronchoscopy provides a less invasive choice with high technical success rate (90-98%) and is effective for central airway obstruction to improve quality of life and survival (10,11,13). The complication is relative rare (3.9%) with few mortality (0.5%) (60). Nevertheless, the benefit is difficult to predict in patients under different situation.…”
Section: Developing Stentsmentioning
confidence: 99%
“…It is well known that airway stenting sometimes causes complications, such as retained secretions, granulation tissue formation, and stent migration (18). Although reported complication rates vary widely among studies, serious complications rarely occur (18,19). The complications in the current study were managed easily and seem to be acceptable.…”
Section: Discussionmentioning
confidence: 53%